Effective project management - Wysocki, Robert K.; Beck, Robert; Crane, David B. (New York : John Wiley and Sons, 2000)
What this book is all about. How to become a world-class project manager. Case study. What is a project? What is project management? Scope the project. Identify project activities. Estimate activity duration, resource requirements, and cost. Construct and analyze the project network diagram...
Keywords: Management; Industrial project management